Strengthening Governance of Social Safety Nets in ASEAN - Giannozzi, Sara; Khan, Asmeen (World Bank, Washington, DC, 2014)
Several Association of Southeast Asian Nation (ASEAN) member states, in the aftermath of the global financial crisis, are expanding their social safety net programs. In many cases, existing delivery mechanisms for social assistance in the region tend to be basic, in line with the small size of programs. This paper is an analytical framework to systematically consider and include governance aspects in the design and analysis of modern social assistance programs. The underlying conceptual model is simple. Programs face a set of supply-side challenges that have to do with their institutional structure and the ways in which accountability and incentive relationships are shaped. However, both in the region and elsewhere in the world there are a number of experiences with diverse governance tools that countries can draw upon as they think how best to design and implement more sophisticated and comprehensive social safety net programs. Finally, administrative capacity is likely to represent a constraint as governments seek to deliver increasingly complex programs to a growing number of beneficiaries over a wide geographically dispersed area. While large investments in administrative capacity are unlikely, it is possible to think about context appropriate solutions that can contribute to reduce governance risk. This report is the first attempt to systematically apply a governance lens to Social Safety Net (SSN) programs in the region. An analytical framework and diagnostic resource to review governance dimensions of SSN programs in ASEAN, the report intends to document existing efforts and challenges and provide guidance to World Bank staff, donors and policy makers interested in strengthening program administration and mitigating potential governance risks within social assistance programs in the region.